Traceability in the alfalfa dehydration chain - Laffi G.; Pasini P. (Quality in lucerne and medics for animal production, 2001)
The recent events that have involved the agricultural and zootechnical sector have evidenced the necessity to focus on the traceability of the productions in order to guarantee, through the direct assumption of responsibility of the producer, quality and genuine goods. SO.PR.E.D., a leading Italian company in the field of forage dehydration has adopted a system which, through compilation of the appropriate file, is able to follow the alfalfa from the growing phase to its working in the factory and its storing in the warehouse for further delivery to the breeder or to the feedstuff producer. The possibility to trace the product that has formed each lot means that each phase of production can be monitored so as to protect the end users.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)